Characterization of paliperidone photodegradation products by LC‐Q‐TOF multistage mass spectrometry. (4th November 2015) - Skibiński, Robert; Komsta, Łukasz; Inglot, Tadeusz
Abstract: The photodegradation of paliperidone in aqueous and methanol media under UVA and UVC irradiation was investigated. The identification and structural elucidation of its photodegradation products were performed by the use of the reversed‐phase liquid chromatography coupled with accurate mass hybrid Q‐TOF mass spectrometry and an atmospheric pressure chemical ionization source. Five degradation products were found and their masses were obtained with high accuracy (1.10–5.26 ppm) based on the TOF (MS) spectra. For the structural elucidation of unknown degradation products MS/MS spectra were also registered. However, for the identification of the main photodegradation product (3‐{2‐[4‐(6‐fluoro‐1, 3‐benzoxazol‐2‐yl)piperidin‐1‐yl]ethyl}‐9‐hydroxy‐2‐methyl‐6, 7, 8, 9‐tetrahydro‐4H‐pyrido[1, 2‐a]pyrimidin‐4‐one) in‐source fragmentation connected with collision‐induced dissociation was used and MS 3 spectra were finally performed. The photodegradation of paliperidone yields the first‐order kinetics in all tested conditions. The aqueous medium was in this case much less stable than the methanol solvent regardless of the irradiation source. Additionally, the toxicity of the analyzed photodegradation products was predicted by the use of ECOSAR software and comparable values of LC50 for the main degradants and the parent compound were obtained. Copyright © 2015 John Wiley & Sons, Ltd.